Large shareholder Expropriation in China's Family-Controlled Listed Companies - Sun, Haibo (2007)
Many studies have been proceeded to measure the degree of large shareholder expropriation. However, most of these literatures have attempted to measure the large shareholder expropriation indirectly by using different proxies. As a result, I attempt to use a direct way to measure large shareholder expropriation. Using a sample of 100 family-controlled listed companies, this dissertation explores large shareholder expropriation behavior in China's family-controlled firms. According to the empirical results, we have found that aggregate measure of large shareholder expropriation is significantly negatively corrected the overall corporate governance level, which means that companies with good corporate governance level tend to have less expropriation of minority shareholders. We also found that that aggregate measure of large shareholder expropriation is significantly negatively correlated with POA, suggesting that as large shareholders' expropriation activities, their holding companies' performance obviously decline. The corporate operating profitability tends to be lower for those companies with more large shareholder expropriation.